Pursuing the good : ethics and metaphysics in Plato's Republic - Cairns, Douglas L.; Herrmann, Fritz-Gregor; Penner, Terry, 1936- (Edinburgh Leventis studies, 2007)
This volume, the fourth in the Edinburgh Leventis Studies series, comprises a selection of papers from the conference held in Edinburgh March 2005 in conjunction with Professor Terry Penner's tenure of the A.G. Leventis Visiting Research Chair in Greek. It brings together contributions from leading Plato scholars from Britain, Europe and North America on a closely defined topic central to Plato's thought and to Ancient Philosophy - Plato's Form of the Good. The importance of the collection lies in the combination and presentation in one place of a range of different approaches to the good in Plato's Republic, and different solutions to the problems posed and proposed by these approaches. The two central issues, which form an underlying thread throughout the collection, are: first whether Plato's Republic is centred on what is good for individual humans, or on some quasi-moral good; and secondly, what the Form of the Good is. Pursuing the Good goes beyond recent studies in the field, and will appeal to classicists and philosophers alike. To the advanced student, it represents a wide-ranging introduction to central issues of Plato's philosophy; for the academic it will provide stimulus through antithetical and controversial solutions to questions old and new.